Mapping the Intellectual Structure and Research Trends of Budgetary Slack - Judijanto, Loso; Kurniawan, Setia Budi (The Es Accounting And Finance, 2025)
This study aims to map the intellectual structure and research trends of budgetary slack through a comprehensive bibliometric analysis of peer-reviewed publications from 1980 to 2024. Utilizing data from the Scopus database and analytical tools such as VOSviewer, the study explores co-citation networks, country collaborations, keyword co-occurrences, temporal evolution, and research density. The results highlight key contributors such as Kenneth A. Merchant and Anthony S. Dunk, foundational theoretical frameworks including agency theory and management control systems, and dominant research themes like participative budgeting, information asymmetry, and performance-based budgeting. A temporal shift is observed from control-based frameworks to behaviorally oriented and contextual themes such as trust, procedural justice, and organizational commitment. The United States remains the central hub of scholarly activity, although research from Asia and the Middle East is increasingly contributing to the discourse. The findings reveal both well-established and underexplored areas, offering valuable direction for future research and practical implications for budgeting practices across organizational settings.